Antibiotic Susceptibility of Staphylococcus Species Isolated in Raw Chicken Meat from Retail Stores - Erinda Lika; Nikola Puvača; Dejan Jeremić; Slobodan Stanojević; Tana Shtylla Kika; Sonila Cocoli; Rosa de Llanos Frutos (Antibiotics, 2021)
The study was aimed at evaluating the presence of antibiotic-resistant Staphylococcus aureus in retailed raw chicken meat from retail stores intended for human consumption. The presence, characterization, and antibiotic susceptibility of S. aureus from 38 retail raw chicken meat samples was performed using a standard microbiological method involving mannitol salt agar (MSA) and Mueller-Hinton agar (MHA). All the samples were positive for Staphylococcus species, of which 34 (89.5%) were positive for S. aureus. The S. aureus isolates were most resistant to tetracycline (88.24%), erythromycin (82.35%), and chloramphenicol (61.77%). Nevertheless, decreased resistance towards gentamycin (23.53%) and cotrimoxazole (38.24%) were recorded. All the S. aureus isolates in this study were resistant to cloxacillin, amoxicillin, and augmentin (amoxicillin + clavulanic acid). The present findings show how the raw chicken meat samples could be a potential source of multidrug-resistant S. aureus strains dissemination. Therefore, this study suggests high-level contamination of meat with multidrug-resistant S. aureus and highlights the public health consequences of consuming such products. Undoubtedly, uncontrolled drugs in food animal production as growth stimulators or medicinal treatment present a possible consequence to people’s health. Having the aforementioned in mind, there is a necessity to control the use of drugs and monitor any residues left in the food intended for human consumption.